"Investigation and assessment of performance and emissions of an IC engine fuelled with diesel and different bio-fuels blended with Ethanol". (2018) - Yerrennagoudaru, Hiregoudar; Manjunatha, K.; Vijaya Kumar, K.R.; Dodda Basavanagouda, M.
Abstract: In view of the existing fossil fuel deposits may come for another 30 to 40 years and Costs of these Fissile Fuels are day by day increasing. As we know that all over the world the diesel vehicle population is growing at an alarming rate. The emission will irritate skin, eyes, nose and throat and also leads to bronchitis asthma in the long run and has been led to air pollution. It is a serious concern with the pollution point of view. Developing Countries like India depends on its fossil fuel requirements on foreign countries for which spars a huge foreign currency in purchase of crude oil. The increasing pressure on crude oil reserves and environmental degradation as an outcome. Hence in view of the above drawbacks there is an urgent need to find an alternative fuels in the existing engines.Fuelslike (Low Cetane Fuels) like Soyabean oil, Canola oil, Plama oil blendedwith ethanol may promise and present a sustainable solution as it can be produced from a wide range of plants and seeds. The present investigation evaluates Ethanol blended with Soyabean oil, Canola oil, Plama oil in CI Engine. A Twin cylinder C I engine adapted to study the brake thermal efficiency, brake specific energy consumption, and emissions In this study, the diesel engine was tested using Diesel and Ethanol blended with Soyabean oil, Canola oil, Plama oil. From this study the emissions like HC, CO2, CO, NOx, Aldehydes, Smokehas been reduced and Ehanol blended with vegetable oils are substitute to diesel fuel.